2022
DOI: 10.1177/07334648221127690
|View full text |Cite
|
Sign up to set email alerts
|

“It Hits Me Right Here at my Heart”: Promoting Emotional Health of Home Care Workers

Abstract: Demand for home and community-based services continues to outpace employment of home care workers (HCWs) who provide this vital assistance. HCWs face challenges that contribute to inadequate staff retention. Of particular concern is the lack of research on HCWs’ emotional health. This research describes facilitators and resources that support HCW emotional health. Qualitative descriptive interviews were conducted with a purposive sample of HCWs ( n = 17) who were formally recognized for their success. Intervie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…9,11,27 This finding is consistent with other recent studies but offers a post-COVID-19 perspective on how these conditions have had lasting outcomes. [39][40][41] It should be noted that HHAs may be coping with stress and poor mood in a variety of ways.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9,11,27 This finding is consistent with other recent studies but offers a post-COVID-19 perspective on how these conditions have had lasting outcomes. [39][40][41] It should be noted that HHAs may be coping with stress and poor mood in a variety of ways.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we found that aspects of the job itself (lack of safety, challenging communication practices, etc) influenced participants’ mood and stress which have been reported as worsening during the COVID-19 pandemic . This finding is consistent with other recent studies but offers a post–COVID-19 perspective on how these conditions have had lasting outcomes …”
Section: Discussionmentioning
confidence: 99%